The geography of trade landscapes of competition and long-distance contacts in Mesopotamia and Anatolia in the Old Assyrian colony period - Palmisano, Alessio (Archaeopress Publishing Ltd, 2018)
A reassessment of the Old-Assyrian trade network in Upper Mesopotamia and Central Anatolia during the Middle Bronze Age, this volume examines exchange networks and economic strategies, continuity and discontinuity of specific trade circuits and routes, and the evolution of political landscapes throughout the Near East.